2007
DOI: 10.1001/archinte.167.9.950
|View full text |Cite
|
Sign up to set email alerts
|

Use of Proton Pump Inhibitors and the Risk of Community-Acquired Pneumonia

Abstract: Background: Recently, the use of proton pump inhibitors (PPIs) has been associated with an increased risk of pneumonia. We aimed to confirm this association and to identify the risk factors. Methods: We conducted a population-based casecontrol study using data from the County of Funen, Denmark. Cases (n = 7642) were defined as all patients with a first-discharge diagnosis of community-acquired pneumonia from a hospital during 2000 through 2004. We also selected 34 176 control subjects, who were frequency match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
255
6
15

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(285 citation statements)
references
References 19 publications
9
255
6
15
Order By: Relevance
“…In a case-control study conducted by Gulmez [47] , 7642 patients with their first diagnosis of community-acquired pneumonia (CAP) were compared with 34 176 healthy controls matched by age and gender from 2000 to 2004. PPI exposure was assessed by determining if the patients had redeemed a prescription for a PPI during the past 90 d. If a prescription had not been redeemed in the past 90 d, the patients were considered to be past users of PPIs and patients who had redeemed a PPI prescription within 90 d were assumed to be current users.…”
Section: Pneumonia: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case-control study conducted by Gulmez [47] , 7642 patients with their first diagnosis of community-acquired pneumonia (CAP) were compared with 34 176 healthy controls matched by age and gender from 2000 to 2004. PPI exposure was assessed by determining if the patients had redeemed a prescription for a PPI during the past 90 d. If a prescription had not been redeemed in the past 90 d, the patients were considered to be past users of PPIs and patients who had redeemed a PPI prescription within 90 d were assumed to be current users.…”
Section: Pneumonia: Literature Reviewmentioning
confidence: 99%
“…The Gulmez study [47] suggested that young, healthy patients who have not had a previous hospital admission and have not been administered antibiotics in the past 90 d are actually at an increased risk of contracting community-acquired pneumonia (Table 2). Unfortunately, this study only included patients who have never had a prior diagnosis of pneumonia.…”
Section: Pneumonia: Literature Reviewmentioning
confidence: 99%
“…Although generally well tolerated, PPI can cause serious adverse reactions. Their short-term use has been associated with infections such as community-acquired pneumonia [18][19][20][21] or Clostridium difficile diarrhea [22,24] due to low gastric acidity, and with a loss of efficacy of clopidogrel as a result of drug interaction [25][26][27][28][29][30]. Longterm use has been related to increases in hip fractures [31][32][33], delayed diagnosis of gastric cancer and increased risk of all-cause mortality [34,35].…”
mentioning
confidence: 99%
“…Une étude cas-témoin nichée dans une cohorte issue d'une base de données de médecine générale hollandaise [13] et une étude castémoin danoise [14] ont conclu à une association entre la prise d'IPP et une augmentation de risque de pneumopathie communautaire. Les hypothèses avancées pour expliquer ce risque de pneumonie communautaire chez les patients sous IPP sont [13] :…”
Section: Pneumonies Communautaires Et Nosocomialesunclassified